PEMBUATAN PIGMEN TITANIUM DIOKSIDA DENGAN MEDIUM KLORIDA[Making Titanium Dioxide through Chloric Acid Leaching] - Solihin, Solihin; Ciptasari, Nurhayati Indah; Arini, Tri (Jurnal Metalurgi, 2012)
THE MAKING OF TITANIUM DIOXIDE PIGMENT WITH CHLORIDE MEDIUM. Indonesia posses huge amount of ilmenit deposits. The ilmenite can be processed to produce titanium dioxide through hydrometallurgical method . The experimental results shows that the iron content in ilmenite can be eliminited through chloric acid leaching, leaving high concentration titanium dioxide as the product. The particle size of ilmenite and chloric acid concentrations affects the elimination rate of iron. The smaller the particle size and the higher the acid concentrations, the higher amount of iron can be eliminated. At 37 % Chloric acid, -200 mesh particle size and 100 °C, the concentrations of TiO2 can be increased up to 88 %.